Complexation Behaviour of Cd(II) with Some Amino Acids and Sulfathiazole at DME - MALHOTRA, VIJAY; SINGH CHANDEL, C.P. (Asian Journal of Chemistry, 2010)
The present manuscript includes the electro-reduction of Cd(II) ion in the aqueous solution with some amino acids (e.g., DL-threonine, DL-isoleucine, L-serine and L-aspartic acid) and sulfathiazole (STA) at dropping mercury electrode (DME) by treatment of Schaap & McMasters method. All the three types of complexes MXY, MXY2 and MX2Y have been found to be reversible and diffusion controlled, involving two electrons in each case (X = amino acid, Y = sulfathiazole). With the help of stability constants of these complexes statistical and electrostatic effects have been considered.